2006
DOI: 10.2337/dc06-0197
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Testosterone Concentrations in Type 1 and Type 2 Diabetes

Abstract: We have recently reported (1) that male patients with type 2 diabetes have frequent hypogonadotrophic hypogonadism. We have now asked whether a similar defect may be observed in type 1 diabetic males to determine whether diabetes per se is the cause of hypogonadotrophic hypogonadism. RESEARCH DESIGN ANDMETHODS -Fifty patients with type 1 diabetes (age range 23-58 years) and 50 age-matched patients with type 2 diabetes (age range 28 -51 years) were included in the study. Patients with known history of hypogonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 11 publications
1
32
1
1
Order By: Relevance
“…However, a few studies have reported that serum SHBG concentrations are also inversely correlated with HbA1c and FPG in both men and women without diabetes (13,15,26), suggesting a relationship between SHBG and glucose homeostasis before the development of diabetes. However, we did not find such a relationship in patients with T2D in this study, which is consistent with the finding of no correlation between blood glucose and HbA1c with serum SHBG in type 1 diabetes (T1D) patients (27). One possible explanation is that in nondiabetic subjects, HbA1c and FPG may be proportionate to the index of insulin resistance whereas the relationship is lost in the state of diabetes.…”
Section: Discussionsupporting
confidence: 79%
“…However, a few studies have reported that serum SHBG concentrations are also inversely correlated with HbA1c and FPG in both men and women without diabetes (13,15,26), suggesting a relationship between SHBG and glucose homeostasis before the development of diabetes. However, we did not find such a relationship in patients with T2D in this study, which is consistent with the finding of no correlation between blood glucose and HbA1c with serum SHBG in type 1 diabetes (T1D) patients (27). One possible explanation is that in nondiabetic subjects, HbA1c and FPG may be proportionate to the index of insulin resistance whereas the relationship is lost in the state of diabetes.…”
Section: Discussionsupporting
confidence: 79%
“…We compared the prevalence of hypogonadism in age matched (mean age 43 years) T1D and T2D men. 6% of T1D mean were hypogonadal as compared to 26% of T2D men [12]. SHBG in T1D was higher than that in T2D men.…”
Section: What Comes First? Hypogonadism or Obesity/mets/t2d?contrasting
confidence: 50%
“…In addition, type 1 diabetes (T1D) is not commonly associated with HH [12]. Thus, clearly HH is a feature related to obesity, insulin resistance and T2D rather than hyperglycemia per se.…”
Section: Introductionmentioning
confidence: 97%
“…hormones were reported previously in T1DM (27,28,29). Although the recruited subjects did not exhibit any clinical sign of hypogonadism or other hormonal disorders, however, we cannot rule out biochemical hormonal abnormalities having not looked at circulating sex hormones.…”
Section: Clinical Studymentioning
confidence: 96%
“…A reduced bone formation as a consequence of reduced osteoblast activity has been identified as the mean pathogenetic effect or for low bone mineral density (BMD) in subjects with T1DM (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39). intimal thickening in atherosclerosis, and Wnt/b-catenin signaling is a regulator of VSMC behavior (9).…”
Section: Introductionmentioning
confidence: 99%